Educators Meet the Fifth Estate: The Role of Social Media in Teacher Training. Issue 14 (November 2019) - Torphy, Kaitlin T.; Drake, Corey
This chapter examines teacher candidates' reflections on engagement with and in social media as it relates to their professional preparation and understandings of teaching within 21st- century classrooms. Extending earlier work, we present the notion of a Fifth Estate within the digital age, redefining network influence. As power and influence are negotiated across executive, judicial, and legislative enterprises, media—the Fourth Estate—and networks of influence among individuals within the Fifth Estate present a new form of educational professionalism. Here, educators, researchers, and the community may engage directly in virtual space. This chapter focuses in particular on the ways that candidates' reflections on the ways in which they seek support from the Fifth Estate are shaped by their visions of teaching and learning, their trust in the teaching professionals who share information in the Fifth Estate, their efficacy to evaluate resources, and their autonomy to select and modify resources.